Technical Innovation and Chest Symmetrizing Techniques in Masculinizing Top Surgery: The Author’s Experience - Patricia A. Bellini, MD, MSc; Daniela B. Corrêa, MD, MSc; Thereza C. Ranção, MD; Mariana S.F. Silva, MD; Luiz Ronaldo Alberti, MD, MSc, PhD; Aleida Nazareth Soares, MSc, PhD (Plastic and Reconstructive Surgery, Global Open)
Background:. Masculinizing top surgery (masculinizing mastectomy, thoracoplasty, or mammoplasty) is the most commonly performed gender-affirming surgical procedure for transmasculine individuals. This study presents 3 surgical chest contouring techniques, along with an innovative approach for optimizing chest symmetry, and provides a flowchart to guide the selection of the most appropriate technique for each patient. Methods:. The medical records of 92 patients who underwent masculinizing top surgery performed by a single surgeon using the free nipple–areolar complex (NAC) graft, NAC flap, or periareolar flap, from 2020 to 2024, were retrospectively reviewed. Technique selection was determined during outpatient evaluations, considering the patient’s body profile, breast volume, degree of ptosis, skin elasticity, and presence of symmastia. Postoperative chest symmetry was also assessed. Statistical significance was defined as a P value of less than 0.05. Results:. The free NAC graft was the most frequently used (47.2%), followed by the periareolar flap and NAC flap techniques. The overall revision rate was low (14.1%), with 4 patients requiring additional procedures to improve chest symmetry, and no significant differences were observed among the techniques. Dehiscence occurred more frequently after the NAC flap procedure (P < 0.016), whereas other complications showed no significant association with any technique. Conclusions:. We demonstrated that safe and aesthetically satisfactory outcomes can be achieved by masculinizing top surgery using the approaches presented. By analyzing the preoperative patient clinical characteristics and outcomes, we developed a flowchart that can guide the selection of the most appropriate surgical technique for each patient’s body profile.